Analisis Kompensasi dan Kompetensi Terhadap Kinerja Karyawan Perusahaan Swasta - Ginting, Daniel; Marnisah, Luis; Halin, Hamid (Journal of Business and Economics Research (JBE), 2025)
This study analyzes the effect of compensation and competence on employee performance at PT. Bramasta Sarana Transportasi. In facing increasingly tight competition in the transportation industry, companies are required to have superior human resources with high performance. Fair compensation and adequate competence relevant to job demands are two key factors that are believed to be able to increase employee productivity. This study uses a quantitative method with a survey approach by distributing questionnaires to selected employees. The findings of the study indicate that compensation and competence have a significant and positive impact on employee performance. These results highlight the importance of companies providing fair compensation policies and continuous competence development through training programs to optimize work performance.